Agricultural debt: How committed are the producers in the Petrolina-Juazeiro region to their debt burdens? (Economia Aplicada, 2015)
This paper is aimed identifying variables for the default on debts of fruit producers of Petrolina/Juazeiro, regarding both public and private sectors. For that, we use a logit model where the producers may “choose” not paying their debts, renegotiate their debts or repay their debts. The probability of producers who decide not to pay their debts to the public sector is over 50%. There are differences in the variables that explain the non-payment to the public sector and the private sector.